Solar-powered nanostructured biopolymer hygroscopic aerogels for atmospheric water harvesting. (February 2021) - Wang, Mengzhu; Sun, Tianmeng; Wan, Dehui; Dai, Ming; Ling, Shengjie; Wang, Jialiang; Liu, Yuqiu; Fang, Ying; Xu, Shuhan; Yeo, Jingjie; Yu, Haipeng; Liu, Shouxin; et al.
Abstract: Solar energy powered sorption-based atmospheric water harvesting (AWH) is a novel strategy for obtaining fresh water in water-scarce regions. The major challenge is to design a cost-effective all-in-one solid bulk sorbent that can capture water from air, even when outdoor conditions are cool, dry, and with low-intensity nature sunlight. Here, we report a strategy comprising solution exchange and lyophilization for integrating a lithium chloride hygroscopic agent, a nanofibrillated cellulose hydrophilic skeleton and a graphene solar absorber, to exploit a solar-powered nanostructured biopolymer hygroscopic aerogel (NBHA) for AWH. The intrinsic porous bilayer structure with interconnected micron- and nano-scale channels of NBHA enables it readily absorb moisture (even at a low relative humidity of ~18%), has a high-water storage capacity, and requires little energy from natural sunlight for solar-driven light-to-vapor conversion. Liquid water was successfully harvested outdoors in natural sunlight of 0.10–0.56 kW m −2 using a facile device based on the NBHA. This work provides a convenient, effective, and practical solution for AWH, even in severe environmental conditions. Graphical Abstract: ga1 A solar-powered nanostructured biopolymer hygroscopic aerogel with a porous bilayer structure comprising of a lithium chloride hygroscopic agent, a wood-derived nanofibrillated cellulose hydrophilic skeleton and a graphene solar absorber was exploited via solution exchange followed by lyophilization strategy, for atmospheric water harvesting. The intrinsic structures and the synergistic effect of the building blocks enable the aerogel with rapid moisture absorption, a large water storage capacity, and solar-driven vapor evaporation. Liquid water was successfully harvested outdoors from the air using a device based on the aerogel, even at low levels of natural sunlight of 0.1–0.6 kW m −2 . Highlights: We use solution exchange combined with lyophilization strategy to exploit nanostructured biopolymer hygroscopic aerogel. The intrinsic porous bilayer structure enables the aerogel robust in atmospheric water harvesting. Liquid water was harvested outdoors in natural sunlight of 0.10–0.56 kW m −2 using a facile device based on the aerogel.